Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2011)
DIRETOR DA REVISTADesembargador Federal Márcio José de MoraesASSESSORASelma Lacerda de AlcântaraEQUIPEConceição Falcone LeiteFrancisco Oliveira da SilvaLucia Massako Y. C. RosaMaria José F. da RochaRenata Bataglia Garcia
Keywords: expediente; v. 22; n. 107; maio/jun. 2011